THE ENDEMIC MARINE FISH FAUNA FROM THE EASTERN PARATETHYS RECONSTRUCTED FROM OTOLITHS FROM THE MIOCENE (MIDDLE SARMATIAN S.L.; BESSARABIAN) OF JURKINE (KERCH PENINSULA, CRIMEA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Reconstructing fossil bony fish faunas using otoliths is a well-established method that allows a diverse and dense record in time and space to be assembled. Here we report about a rich otolith-based fish fauna from the middle Sarmatian s.l. (middle Bessarabian) from Jurkine, Kerch Peninsula, Crimea. The study is based on more than 5,000 specimens constituting 36 different species, 24 of which are new and 2 remain in open nomenclature. This assemblage represents the first major otolith association described from the Bessarabian. It also represents a fish fauna from the last continuous restricted marine environment that evolved in the Eastern Paratethys, was recruited from the Badenian/Tarkhanian fauna, and was not affected by the subsequent Khersonian crisis. The association of otoliths is characterized by a high content of endemic fishes that derived from the relatively well-known early Sarmatian s.l. (Volhynian) fish fauna, and it contains certain faunal elements that were trapped in the then-secluded Eastern Paratethys and did not range into younger strata. This forced endemic evolution explains the unusually high percentage of new taxa.            The fish fauna is dominated by stenohaline marine shelf fishes apparently recruited from the Konkian and earlier Sarmatian s.l. (Volhynian) fauna after the Karaganian crisis. The families Gobiidae and Gadidae benefited most in this restricted marine environment, while deep-water fishes disappeared with the Karaganian crisis. In this study, we discuss the further evolution of Eastern Paratethyan fishes as far as can be reconstructed from the relatively limited data from post-Bessarabian strata, and we also outline targets for future research in the field.The stratigraphic sequence of the Jurkine section is being revised based on a detailed suite of benthic foraminifera. Implications for the stratigraphy of the middle and upper Sarmatian s.l., their boundary, and the paleoenvironments of this part of the Kerch Peninsula are discussed.
Keywords: Crimea; Bessarabian; otoliths; foraminifera; Eastern Paratethys; endemic evolution; Gobiidae; Gadidae